Application for Searching Incoming and Outgoing Letters at the Bengkulu Provincial Dprd Office by Applying the Sequential Searching Algorithm - Ardi Prawinata; Leni Natalia Zulita; Ricky Zulfiandy (Jurnal Komputer, Informasi dan Teknologi, 2021)
Processing and archiving incoming and outgoing letters at the Bengkulu Provincial DPRD still uses the manual method, namely by taking notes (handwriting) on ​​a book and reviewing the order of previous letters to number the new letters that will come out and for incoming incoming letters to be recorded first. prior to disposition. The search application for incoming and outgoing letters at the Bengkulu Provincial DPRD Office was made to facilitate the process of incoming and outgoing letters by entering keywords, where in the search process a Sequential Searching Algorithm was applied which was used to analyze keywords with the data contained in the database. The search application for incoming and outgoing letters at the Bengkulu Provincial DPRD Office can display the output of incoming and outgoing mail data reports so that it can make it easier to archive reports. The application for searching incoming and outgoing letters at the Bengkulu Provincial DPRD Office was created using the Visual Basic .Net programming language and SQL Server 2008r2 Database. Based on the results of black box testing, the functionality of the incoming and outgoing mail search application at the Bengkulu Provincial DPRD Office has been running properly and is able to display search results for incoming and outgoing letters based on the desired keywords.